2017
DOI: 10.1111/tpj.13568
|View full text |Cite
|
Sign up to set email alerts
|

Sugar and hexokinase suppress expression of PIP aquaporins and reduce leaf hydraulics that preserves leaf water potential

Abstract: Sugars affect central aspects of plant physiology, including photosynthesis, stomatal behavior and the loss of water through the stomata. Yet, the potential effects of sugars on plant aquaporins (AQPs) and water conductance have not been examined. We used database and transcriptional analyses, as well as cellular and whole-plant functional techniques to examine the link between sugar-related genes and AQPs. Database analyses revealed a high level of correlation between the expression of AQPs and that of sugar-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 103 publications
(181 reference statements)
0
26
0
2
Order By: Relevance
“…The apoplastic pathway via cell walls is often implicitly assumed to be the major pathway of water transport through the outside xylem (Buckley, 2015). However, the observation of aquaporin-mediated water transport in BS using aquaporin mutants means that the symplastic pathway is in fact plausible (Sade et al, 2010(Sade et al, , 2014Prado et al, 2013;Kelly et al, 2017). Other evidence for symplastic water transport comes from the diurnal rhythms in K leaf , and the dynamic response of K leaf to environmental changes including temperature and light intensity.…”
Section: Outside-xylem Water Transport (K Ox )mentioning
confidence: 99%
“…The apoplastic pathway via cell walls is often implicitly assumed to be the major pathway of water transport through the outside xylem (Buckley, 2015). However, the observation of aquaporin-mediated water transport in BS using aquaporin mutants means that the symplastic pathway is in fact plausible (Sade et al, 2010(Sade et al, , 2014Prado et al, 2013;Kelly et al, 2017). Other evidence for symplastic water transport comes from the diurnal rhythms in K leaf , and the dynamic response of K leaf to environmental changes including temperature and light intensity.…”
Section: Outside-xylem Water Transport (K Ox )mentioning
confidence: 99%
“…The results indicated the role of chloroplasts in the regulation of the increase in leaf area, depending on the access to sugars [40]. The effects of sugars on plant aquaporins (and water conductance) have recently been examined; it was observed that glucose reduces the movement of water from the xylem to the mesophyll [41], which could also affect leaf growth. It has also been shown that sugars (such as, glucose and sucrose) can affect the movement of cellular organelles, including chloroplasts [42,43].…”
Section: Introductionmentioning
confidence: 96%
“…As for SD, in LD CAA levels are relatively unchanged by light dose in wild type and gin2 . Earlier studies have reported that HXK1 transcript abundance is upregulated by glucose application ( Price et al, 2004; Yang et al, 2013; Kelly et al, 2017 ). In both our SD and LD conditions we do not observe a fluence rate dependent regulation of HXK1 transcript levels.…”
Section: Resultsmentioning
confidence: 99%